How Dutch professionals conduct interactive design sessions to foster 'shared understanding'. (May 2016) - van Dijk, Terry; Ubels, Hiska
In the pursuit of the communicative, collaborative and participatory planning processes advocated by academic planning literature, a practice has evolved that translates abstract objectives into practical workforms. Planning literature proposes many objectives that can be met by less top-down methods of generating ideas and making decisions. Little is known about how such objectives are translated into practical methods applied. This paper presents an inventory of practices that is meant to validate and supplement available theories on communicative planning. It concentrates on a specific part of the planning process: the moment where optional solutions to a problem are being generated, not by each stakeholder in isolation, but specifically by groups of stakeholders in constructive designerly interaction with each other. We interviewed 11 experienced professionals from the Netherlands who use interactive design sessions on a regular basis. This paper reports on their responses to questions about skills needed by session leaders, what types of venues are best to use, how to behave during sessions, requirements for participants to contribute, roles of governments and what explains the eventual effects of session outcomes. Although every session still needs to be tailor-made, based on practical wisdom and sensitivity to context, this study reveals recurring hands-on principles for organizing an effective dialogue for exploring solution space.